STRUCTURAL ORGANIZATION OF INTERSTITIAL LEYDIG CELLS AND SERTOLI CELLS IN EXPERIMENTAL CHEMICAL CASTARATION AT THE EARLY STAGES OF MONITORING IN RATS - Stetsuk, E.V.; Goltsev, A.M.; Shepitko, V.I. (World of Medicine and Biology, 2018)
Detailed electronmicroscopic studies of Sertoli cells and Leydig cells in the testes of sexually mature male “Wistar” rats of the intact group were carried out. The features of the Sertoli cells and Leydig cells structure organization in the experimental chemical castration with goserillin in the first month of the study are described.
Keywords: testis; Sertoly cells; Leydig cells; rats